2013
DOI: 10.1111/vcp.12067
|View full text |Cite
|
Sign up to set email alerts
|

Breed‐specific biochemical reference intervals for the adult Dogue de Bordeaux

Abstract: Specific reference intervals for biochemical analytes in the Dogue de Bordeaux were determined under controlled pre-analytical and analytical conditions, and according to international recommendations. The use of these breed-specific reference intervals is recommended when using the specified analytic instruments, especially for the 6 analytes for which the reference intervals differed considerably from those provided by manufacturers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…The need for breed‐specific RIs is increasingly discussed in veterinary medicine . The rationale behind partitioning is the decrease in the variability of the reference population and the subsequent narrowing of RIs.…”
Section: Discussionmentioning
confidence: 99%
“…The need for breed‐specific RIs is increasingly discussed in veterinary medicine . The rationale behind partitioning is the decrease in the variability of the reference population and the subsequent narrowing of RIs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively low number of dogs finally included in the reference population, the nonparametric method of RI determination could be used, as recommended by the IFCC‐CLSI . Because of the low number of dogs in some subgroups, the effects of covariables such as age, sex, and color of face mask may have been underestimated; however, as previously discussed, the reference sample group was still considered representative of the French and Belgian population of DDBs; DDBs aged > 6 years and with black face mask are indeed not frequent …”
Section: Discussionmentioning
confidence: 99%
“…As previously described, blood sampling in this study was highly standardized, and performed by the same experienced veterinarians under similar conditions . The K3‐EDTA tubes were kept refrigerated at 4°C, and analyses were performed within 12 h. Several studies have demonstrated the good stability of canine hematology variables in whole blood stored in EDTA tubes at 4°C for up to 24 h .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inherent risks of CSF collection, the goal was to attain the minimum number of participants required to establish an appropriate RI while minimizing risk to healthy dogs . At least 40 reference individuals were enrolled for each RI (serum total LD, n = 41; serum isoenzymes, n = 40; CSF total LD, n = 40; CSF isoenzymes, n = 42) to perform nonparametric statistics, as enzymes often have non‐Gaussian distributions . This study received approval from Washington State University's Institutional Animal Care and Use Committee and met all institutional standards.…”
Section: Methodsmentioning
confidence: 99%